2021
DOI: 10.3892/mmr.2021.12217
|View full text |Cite
|
Sign up to set email alerts
|

COVID‑19 vaccination and IgG and IgA antibody dynamics in healthcare workers

Abstract: Given the current outbreak of coronavirus disease 2019 and the development and implementation of mass vaccination, data are being obtained by analyzing vaccination campaigns. in the present study, 69 healthcare workers who were exposed to patients with severe acute respiratory syndrome coronavirus-2 were monitored for specific immunoglobulin (Ig)G and IgA levels at different time periods. Prior to vaccination, after the first round of vaccination at 21 days (when the second dose of vaccine was administrated) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 39 publications
6
42
0
Order By: Relevance
“…This study showed that age was correlated with the amount of anti-SARS-CoV-2 IgG and that IgG levels were higher in younger participants. This may be related to the viability of immunity in the younger population compared with that of older populations, which has been shown in previous studies on other vaccines [ 37 , 38 ]. Younger individuals tend to have more T and B cells related to adaptive immunity and active toll-like receptor reactions, which have a greater association with higher IgG levels among younger individuals than older individuals [ 37 , 39 ].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This study showed that age was correlated with the amount of anti-SARS-CoV-2 IgG and that IgG levels were higher in younger participants. This may be related to the viability of immunity in the younger population compared with that of older populations, which has been shown in previous studies on other vaccines [ 37 , 38 ]. Younger individuals tend to have more T and B cells related to adaptive immunity and active toll-like receptor reactions, which have a greater association with higher IgG levels among younger individuals than older individuals [ 37 , 39 ].…”
Section: Discussionmentioning
confidence: 77%
“…The second dose can trigger systemic inflammation, and recipients with strong immunity are more likely to experience systemic symptoms. Previous studies have reported the association between the presence of adverse reactions and the IgG titer [ 33 , 37 ]. However, they did not clearly show the association between concrete adverse effects and IgG titers.…”
Section: Discussionmentioning
confidence: 99%
“…However, even though some studies have suggested that IgG titers in vaccinated individuals decline over time, the exact rate of this decline in IgG titers or the critical titer level up to which they can still be considered as adequately protected from infection and disease, remain unclear ( 38 ). At this point, it should be emphasized that the immune system may produce a series of antibody variants, each with a different neutralizing capacity, depending on the exact target-epitope ( 39 - 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, a significant decrease in antibody titers was observed at 3 months compared with the peak response, with the antibody response being higher in seropositive compared with initially seronegative participants ( 41 ). A second study was also performed, enrolling a homogenous healthcare workers group in Romania, in an attempt to investigate the immunity status of subjects having received the BNT162b2 mRNA COVID-19 vaccine as well ( 42 ). In this framework, it was found that following the first vaccination dose, the IgG levels in non-infected subjects exhibited an increase of ~12-fold in males and one of ~11-fold in females; however, following the second round of vaccination, the IgG levels increased 1.33-fold in males and 2.11-fold in females, when compared with those after the first dose ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation